(untitled) (International Journal of Physiotherapy, 2025)
Background: Stroke often results in significant impairment of proprioception, which is the sensation of body position and movement in space. This impairment can lead to difficulties with motor coordination and balance. The main objective of this review is to provide a concise summary of the significance of proprioception and its relationship with the stroke population from critically published research papers. Specifically, the review aims to determine the influence of lower limb proprioception following a stroke and the efficacy of proprioceptive training in enhancing balance among stroke patients. Methods: This systematic review explores the effects of stroke on proprioception and delves into the role of physical therapy interventions in enhancing proprioceptive function in the lower limbs post-stroke. It includes studies examining post-stroke proprioceptive impairments in lower limbs and physical therapy interventions, such as sensory re-education and balance training. Eligible studies include RCTs and observational studies with adult participants. Sources include PubMed, Embase, Cochrane Library, and CINAHL, covering publications from 2015 to 2024. Results: A total of 12 studies involving 236 participants were included in the review. The studies varied in design, with most being randomized controlled trials. Interventions included sensory re-education, balance training, and proprioceptive exercises targeting the lower limbs. Stroke survivors often experience lower limb impairments affecting mobility, including proprioceptive deficits, spasticity, and weakness. Studies advocate proprioceptive training, including robotic-assisted therapy, virtual reality, and exercises, to enhance recovery. Techniques like mirror therapy, motor imagery, and Transcutaneous Electrical Nerve Stimulation (TENS) showed promise in improving gait speed, balance, and neurostimulation outcomes. Coordinating proprioceptive pathways with muscular synergies is crucial for postural control. Emerging therapies, including telerehabilitation and neurostimulation, highlight the potential for innovative approaches in stroke rehabilitation and functional recovery. Conclusion: This review highlights that targeted physical therapy interventions, such as sensory re-education and balance training, significantly improve stroke survivors’ proprioception, balance, and motor function, promoting better functional recovery. These findings emphasize the critical role of proprioceptive-focused rehabilitation in enhancing patient outcomes. However, limitations include methodological variability, small sample sizes, and heterogeneity in intervention approaches, which may limit generalizability. Future research should prioritize standardized protocols, larger participant cohorts, and long-term follow-ups to refine and validate effective rehabilitation strategies.